Application of Carbon Dioxide Snow in Machining of CGI using an Additively Manufactured Turning Tool - Thomas Heep; Christian Bickert; Eberhard Abele (Journal of Manufacturing and Materials Processing, 2019)
The application of conventional cooling lubricants for the tribological conditioning of machining processes involves high additional costs and health risks. The application of a cryogenic carbon dioxide (CO2) snow cooling strategy is an economical and environmentally sound alternative for oily cooling emulsions since it has a high cooling effect as well as a residue-free sublimation. This article introduces a laser additive manufactured tool holder with an integrated dual nozzle which enables CO2-snow jet application. Initially this work focuses on the characterization and the selection of a suitable nozzle geometry. The modular tool body features an adapted channel structure for process-reliable and targeted CO2-snow cooling for turning processes. This enables the simultaneous cooling of the rake and flank face with CO2-snow, as well as the application of cryogenic multi-component cooling of the rake face. In the context of this study, the focus lies on the technological evaluation of three different supply strategies during the continuous turning of compacted graphite iron CGI-450 at increased cutting speed. It was established that an efficient rake face cooling is indispensable to achieve a low thermal tool load, and thus lower crater wear behavior. Therefore, this study contributes to an improvement in cryogenic machining processes regarding the design of additively manufactured tool bodies for process-reliable CO2-snow cooling, as well as for the selection of supply strategies to minimize the thermomechanical tool load.